Fundamentals Of Farm Business Management - S.S. Johl; T.R. Kapur (New Delhi Kalyani)
This book may be immense value and interest to the product to the professionals, industry people and scientist of this field.
Farm Management Farm Resources Product Relationship
Keywords: Farm Management; Farm Resources; Product Relationship